Five new species of Anthurium (Araceae) from the Caribbean Forests of Panama. Issue 1 (2nd January 2017) - Ortiz, Orlando O.; Croat, Thomas B.
Abstract: Five new species of Anthurium are described as new to science from the Caribbean slope of Panama: Anthurium alvinii, Anthurium baldinii, Anthurium cerrofrioense and Anthurium santamariae are known only from Bocas del Toro Province and Anthurium cerrosantiagoense is known only from Comarca Ngäbe-Buglé.